Cold H i ejected into the Magellanic Stream. Issue 1 (8th June 2020) - Dempsey, J; McClure-Griffiths, N M; Jameson, K; Buckland-Willis, F
ABSTRACT: We report the direct detection of cold H i gas in a cloud ejected from the Small Magellanic Cloud (SMC) towards the Magellanic Stream. The cloud is part of a fragmented shell of H i gas on the outskirts of the SMC. This is the second direct detection of cold H i associated with the Magellanic Stream using absorption. The cold gas was detected using 21-cm H i absorption-line observations with the Australia Telescope Compact Array (ATCA) towards the extra-galactic source PMN J0029−7228. We find a spin (excitation) temperature for the gas of 68 ± 20 K. We suggest that breaking super shells from the Magellanic Clouds may be a source of cold gas to supply the rest of the Magellanic Stream.